WAYS TO INCREASE THE EFFICIENCY OF WORK ON ARTISTIC TEXTS IN PRIMARY CLASSES - Nazirova Shakhnoza Odinajon kizi (Web of Journals Publishing, 2024)
In this article, the issues of formation and development of hermeneutic abilities of elementary school students with the help of artistic texts are considered, and effective methods are described.
Keywords: work of art, hero of the work, folklore, fairy tale, proverb, episode, image, subject, plan, conclusion.